Đặc điểm các bãi bồi hiện đại ven biển Đồng bằng Bắc Bộ - Hồng, Lê Xuân (Vietnam Journal of Earth Sciences, 2001)
The characteristics of the present accumulation segments in the coastal shoreline of the Bac Bo delta